2018
DOI: 10.1088/1361-665x/aacf79
|View full text |Cite
|
Sign up to set email alerts
|

Design and testing of a passively adaptive inlet

Abstract: Mechanical instabilities and elastic nonlinearities are emerging engineering means for designing shape-changing devices. In this paper, we exploit the taxonomy of post-buckling behaviours of a glass-fibre panel to design an adaptive air inlet that passively regulates the fluid flow into a connected duct. The adaptive component controls the inlet aperture by snapping open and closed depending on the velocity and pressure of the surrounding fluid. Sensing, actuation and control is entirely governed by the charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…By increasing the amount of compression beyond the limit point on the broken-away path, the inlet can be transformed into a bistable structure that remains closed once the airflow is reduced. The greater the applied compression, the higher the airspeed required to actuate snap-through; the system's parameters can be tailored to meet specific operating requirements (see [98,99] for further details).…”
Section: Adaptive Structuresmentioning
confidence: 99%
“…By increasing the amount of compression beyond the limit point on the broken-away path, the inlet can be transformed into a bistable structure that remains closed once the airflow is reduced. The greater the applied compression, the higher the airspeed required to actuate snap-through; the system's parameters can be tailored to meet specific operating requirements (see [98,99] for further details).…”
Section: Adaptive Structuresmentioning
confidence: 99%
“…However, this narrative has been challenged more recently, and instabilities have been exploited for novel functionalities. This has led to the creation of well-behaved nonlinear structures [5] such as shape-adaptive structures [6][7][8][9], deployable structures [10][11][12], zero or negative stiffness structures [13,14], energy harvesters [15], as well as non-destructive testing techniques [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…From a macroscopic point of view, recent studies have indicated that a flexible material can be adopted to control the fluid (including both gas and liquid) flow in fluidic devices. In this kind of flexible fluidic device, the fluid flow and the wall deformation are coupled to each other. Comparing with the rigid fluidic device, the flexible wall plays an important role in solid–fluid coupling behaviors, which might further be harnessed for the control of the fluid flow process.…”
Section: Introductionmentioning
confidence: 99%